Analyzing Message Campaign “Waste Down Beauty Up”, Advertising, and Electronic Word of Mouth in Forming Generation Z Purchase Intention - May Roni; Clara Monica Edira; Nur Efendi (Universitas Nusa Putra, 2025)
Indonesia's beauty industry has experienced rapid growth, particularly as more Generation Z consumers purchase beauty products. As competition increases, companies are using new marketing strategies. For instance, Sociolla launched the “Waste Down Beauty Up” campaign and uses electronic word of mouth through its Sociolla Connect platform. This study examines the impact of advertising, message campaigns, and electronic word of mouth on purchase intention, both individually and in combination. The research employed a quantitative approach, utilizing questionnaires, and the data were analyzed using SPSS version 26. The findings indicate that advertising and message campaigns do not have a significant effect on their own; however, electronic word of mouth has a positive and significant impact on purchase intention. When combined, all three factors influence purchase intention. These results highlight the importance of electronic word of mouth. Companies should encourage customers to share positive reviews on digital platforms to boost purchase intention.